The "Jesus-Mozi Dialogue" In The Revival of Mohism In The Republic Of China——Take Zhang Yijing, Wang Zhixin And Wu Leichuan As Examples - HUANG, Jiaofeng (International Journal of Sino-Western Studies, 2021)
"Jesus-Mozi Dialogue" is an underflow in the revival of Mohism in the Republic of China. Since modern times, the intellectual circles have mostly taken Christianity as the "rational model" of Mohism. When it comes to the best reference for Christianity in traditional Chinese culture, Mohism is always used as an example, which has been discussed in the field of Mohism research. However, in the past, people still paid little attention to the church’s view of the "Jesus-Mozi Dialogue" between Mohist School and Chinese Christians, which is a pity. This article attempts to discuss the various viewpoints of Zhang Yijing, Wang Zhixin, and Wu Leichuan on Mohism and "Mohist religion" as examples, and looks forward to giving a clear definition of the literature and the division of school attribution to the results of the "Jesus-Mozi Dialogue".